PERANCANGAN DAN PEMBUATAN DIVAIS SENSOR GAS CO BERBASIS INDIUM TIMAH OKSIDA (ITO) DENGAN TEKNOLOGI LAPISAN TIPIS - Slamet Widodo; Goib Wiranto (Research Center for Chemistry - LIPI, 2015)
In this paper it will be described the design and manufacturing of microdevice to be used as platform for Carbon monoxide (CO) gas sensor based on indium tin oxide (ITO). The device has been designed on silicon substrate with an active area of 3x3 mm2 , and consisted of bonding pad, heater, electrode, and temperature sensor components. The minimum feature size used is 50 microns, as allowed by the capability of photolithographic process. The formation of microdevice structure has been done mainly using lift-off technique on platinum (Pt) layer, which was deposited by DC sputtering with aluminium (Al) as sacrificial layer. The overall chip dimension is not more than 5x5 mm2. The measurement conducted to study the resistance versus temperature characteristics has shown that the heater and temperature sensor elements have functioned as expected, in which their resistances change linearly with an increase in substrate temperature between 20 – 200 oC. The range of increase in resistance values for the heater is 500 – 1000 ohm, whereas for the temperature sensor is 100 – 300 ohm.Keywords: Microdevices, lift-off process, sputtering, electrode, heater, gas sensor, ITO, CO gas.